Use of a clinical pathway to improve the acute management of vaso‐occlusive crisis pain in pediatric sickle cell disease. Issue 4 (19th November 2013) - Ender, Katherine L.; Krajewski, Jennifer A.; Babineau, John; Tresgallo, Mary; Schechter, William; Saroyan, John M.; Kharbanda, Anupam
<x xml:space="preserve">Abstract</x> Background The most common, debilitating morbidity of sickle cell disease (SCD) is vaso‐occlusive crisis (VOC) pain. Although guidelines exist for its management, they are generally not well‐followed, and research in other pediatric diseases has shown that clinical pathways improve care. The purpose of our study was to determine whether a clinical pathway improves the acute management of sickle cell vaso‐occlusive crisis (VOC) pain in the pediatric emergency department (PED). Procedure Pain management practices were prospectively investigated before and after the initiation of a clinical pathway in the PED of an urban, tertiary care center with 50, 000 ED visits per year and approximately 200 active sickle cell patients. The pathway included instructions for triage, monitoring, medication administration, and timing of assessments and interventions. Data were eligible from 35 pre‐pathway and 33 post‐pathway visits. Primary outcome was time interval to administration of first analgesic medication. Statistical analysis was by Student's t‐test, using natural‐log‐transformed data for outcomes with skewed distribution curves. Results Time interval to first analgesic improved from 74 to 42 minutes (P = 0.012) and to first opioid from 94 to 46 minutes (P = 0.013). The percentage of patients who received ketorolac increased from 57% to 82% (P = 0.03). Decrease in time interval to subsequent pain score assessment was not statistically significant (110 to 72 minutes (P = 0.07)), and change in pain score was not different (P = 0.25). Conclusions The use of a clinical pathway for sickle cell VOC in the PED can improve important aspects of pain management and merits further investigation and implementation. Pediatr Blood Cancer 2014;61:693–696. © 2013 Wiley Periodicals, Inc.